Peran Sosial Digital dan Teman Sebaya Terhadap Penggunaan Bahasa Non-Baku pada Anak Usia 5 Tahun - Rana Nurjanah (Universitas Muhammadiyah Mataram, 2026)
The phenomenon of the language development of Generation Alpha children in the digital era needs to be studied sociolinguistically, considering that the language characteristics of this generation are influenced by social media and their direct social environment. This study uses a descriptive qualitative approach to examine the influence of the digital social environment and peers on the language use of 5-year-old children, focusing on variations of popular slang such as skibidi, sigma, and code-mixing between Indonesian and foreign terms. Data were obtained through observation, indirect interviews, and documentation of daily speech. The analysis shows that children's vocabulary is significantly influenced by digital content and social interactions, which function as markers of social identity and communication tools within peer groups. This research enriches sociolinguistic studies, especially in the context of children's language development in the digital era.